EVALUASI SISTEM PEMBERIAN KREDIT STUDI KASUS PADA PT BPR ASIA BINTANG CEMERLANG - Rahayu, Sri; Tambunan, Debora; Pasaribu, Deby Siska Oktavia (MTU PRESS, 2025)
The purpose of this study is to determine: 1) Whether the credit granting system implemented by PT BPR Asia Bintang Cemerlang is appropriate according to the existing theory. 2) Whether the internal control system of credit granting implemented by PT BPR Asia Bintang Cemerlang is effective. This type of research is a case study. Data collection techniques used are interviews, documentation and questionnaires. To answer the first problem, it is done by comparing the credit granting system according to the theory with the credit granting system that exists in PT BPR Asia Bintang Cemerlang. Meanwhile, to answer the second problem, namely by analyzing the implementation of internal control and with compliance testing using the Stop-or-go Sampling method with the following steps: 1) determining the attributes to be examined, 2) determining the population to be sampled, 3) determining the level of reliability and DUPL, 4) determining the first sample to be taken, 5) creating a Stop-or-go Decision table. Based on the results of the data analysis, it can be concluded that the credit granting system in PT BPR Asia Bintang Cemerlang Medan is in accordance with the underlying theory and the internal control system implemented by PT BPR Asia Bintang Cemerlang Medan is effective. This can be seen from the fulfillment of the elements in existing internal control and from compliance testing of samples, no errors were found or errors were equal to 0.